Vorošilov, Gorkij, Mikojan and Jaroslavskij (f.l.t.r.) in the Dinamo-stadium, in Moscow at a outing of the Krasnaja Presnja Komsomol (1929)
Vorošilov, Gorkij, Mikojan and Jaroslavskij (f.l.t.r.) in the Dinamo-stadium, in Moscow at a outing of the Krasnaja Presnja Komsomol.